(untitled) (Applied Biological Research, 2013)
Polyclonal antisera were raised against bovine somatotropin (ST) in rabbits and high titer achieved in less than 40 days after primary immunization. Protocol was developed with slight modification in method of Hu (2002) for antisera production and booster injection given on 28th and 37th day. The serum for antibody titer was collected on 35th and 42nd day. The antisera procured were effective in Western blotting and for purification of ST using affinity column chromatography.